Building Inclusive Education: Contribution of Teachers at Kindergarten Aisyiyah 85 for Children with Special Needs - Hasanah, Hasanah; Rahma, Jamiatur; Fatihatur Rizqiyah, Farah (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
This study is entitled The Role of Teachers in Implementing the AUDBK Curriculum at Aisyiyah 85 Trensains Kindergarten using descriptive qualitative research. With the research subject Aisyiyah 85 Trensains Kindergarten which has more than 60 children. This observation aims to find out the curriculum applied by the school. The results of this study are that researchers found that through this inclusion program the role of the teacher in improving children's social abilities is as a motivator and innovator in responding to children's difficulties, as well as a facilitator who is able to provide good and appropriate facilities to children with special needs at Aisyiyah 85 Trensains Kindergarten. In addition, Aisyiyah 85 Trensains Kindergarten also applies the appropriate curriculum, facilities and infrastructure, and learning methods so that children's growth and development develop well. The curriculum applied is not the AUDBK curriculum but uses an independent curriculum, because the ABK children in Aisyiyah 85 Trensains Kindergarten are classified as mild ABK, it's just that the level of achievement standards is lowered a little from the general standard. The research method used is a descriptive qualitative approach with data collection techniques observation or observation, interviews with principals and class teachers and documentation of classroom activities. While data analysis uses the Miles and Huberman approach, namely data reduction, data presentation, and conclusion drawing. This research was conducted at Aisyiyah 85 Trensains Kindergarten, South Tangerang Regency, Banten Province. Penelitian ini berjudul Peran Guru dalam Penerapan Kurikulum AUDBK pada TK Aisyiyah 85 Trensains dengan menggunakan penelitian deskriptif kualitatif. Dengan subjek penelitian TK Aisyiyah 85 Trensains yang mempunyai jumlah siswa sebanyak 60 lebih anak. Observasi ini bertujuan untuk mengetahui kurikulum yang diterapkan oleh sekolah. Adapun hasil dari penelitian ini yakni peneliti menemukan bahwa melalui program inklusi ini peran guru dalam meningkatkan kemampuan sosial anak yakni sebagai motivator dan inovator dalam menanggapi kesulitan anak, serta sebagai fasilitator yang mampu mmberikan fasilitas yang baik dan tepat kepada anak berkebutuhan khusus di TK Aisyiyah 85 Trensains. Selain itu, lembaga TK Aisyiyah 85 Trensains juga menerapkan kurikulum, sarana dan prasarana, serta metode pembelajaran yang sesuai sehingga pertumbuhan dan perkembangan anak berkembang dengan baik. Kurikulum yang diterapkan bukan kurikulum AUDBK namun menggunakan kurikulum merdeka, karena anak ABK yang ada di TK Aisyiyah 85 Trensains tergolong ABK ringan, hanya saja untuk tingkat standar pencapaiannya diturunkan sedikit dari standar umum seharusnya.Metode Penelitian yang digunakan merupakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data observasi atau pengamatan, wawancara kepada kepala sekolah dan guru kelas dan dokumentasi kegiatan di kelas. Sedangkan analisis data menggunakan pendekatan Miles dan Huberman, yakni reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini dilaksanakan di TK Aisyiyah 85 Trensains Kabupaten Tangerang Selatan Provinsi Banten.